THE COMPLEMENT FIXATION TEST IN THE DIAGNOSIS OF VIRUS INFECTIONS OF THE CENTRAL NERVOUS SYSTEM - Casals, J. (The Rockefeller University Press, 1941)
A specific complement fixation test can be obtained in various central nervous system virus infections by using as antigens emulsions of infected brain tissue, freezing and thawing the brain emulsion, and then centrifuging it in an angle head centrifuge at 3500 R.P.M. for 1 hour. The method has proved reliable in the case of rabies, St. Louis encephalitis, Japanese B encephalitis, lymphocytic choriomeningitis, Eastern equine encephalomyelitis, Western equine encephalomyelitis, louping ill, and spontaneous encephalomyelitis of mice (Theiler's disease). The specificity of the reaction, regardless of the virus involved, requires different temperatures of inactivation of the sera according to animal species: 56°C. for guinea pig, 60°C. for mouse, and 65°C. for rabbit and dog sera, all heated for 20 minutes. For human sera a temperature of inactivation of 60°C. also for 20 minutes has been adopted; at this temperature the reaction is in general specific. Complement-fixing antibodies in high titre were found in the sera of rabbits, guinea pigs, mice, and dogs immunized with rabies virus. Complement-fixing antibodies were present in high titre in sera drawn from two persons 8 years after an attack of louping ill, from five persons 2½ years after an attack of Eastern equine encephalomyelitis, and from two persons 2½ years after Western equine encephalomyelitis. In cases of St. Louis encephalitis and lymphocytic choriomeningitis, complement-fixing antibodies have been found shortly following infection but not after long periods.